2018
DOI: 10.4081/cp.2018.991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cameriere’s and Demirjian’s Methods of Age Estimation among Children in Kerala: A Pilot Study

Abstract: The aim was to compare age estimation using Cameriere’s and Demirjian’s methods to chronologic age in children with mixed dentition in a rural population of Kerala. The present study comprised of 10 subjects of age range 7-12 years. Dental age was assessed using Cameriere’s and Demirjian’s methods and was compared to the chronologic age. Panoramic radiographs were used for assessment of dental age. Data were analysed using paired t-test. The mean of difference obtained was 0.92 and the pvalue was 0.172 which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As this method only requires open apices and teeth length to be measured, it is easier, and more objective compared to other quantitative methods. Some previous study showed that Cameriere's method is more accurate than the widely used Demirjian's or Willems's methods [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…As this method only requires open apices and teeth length to be measured, it is easier, and more objective compared to other quantitative methods. Some previous study showed that Cameriere's method is more accurate than the widely used Demirjian's or Willems's methods [34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Development of permanent teeth is a very useful for age estimation method in children. Age estimation in children based on dental development is preferred to methods based on skeletal maturation as the calcification in the teeth is controlled by genes rather than environmental factors (Nair et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the assessment of the dental age, the Demirjian method was used because even though it may indicate differences between the chronological age and dental age, it remains the most used method for determining the dental age [ 28 ]. A number of studies suggest that the method tends to overestimate the age in different populations and that the values need to be adapted for each investigated group [ 29 , 30 ]. In the studied sample of patients, differences were found between dental age and chronological age, but no statistical tests were performed, since the purpose of the study was not to analyze the accuracy of the Demirjian method.…”
Section: Discussionmentioning
confidence: 99%